Santa Paws on Christmas Island - Edwards, Kris. (New York : Scholastic, 2006)
Santa Paws and the Callahan family are spending Christmas on a sunny Florida island. While the family tries to enjoy their vacation, Santa Paws is hard at work saving the day.
"An Apple paperback"--T.p.
Keywords: Rescue dogs -- Juvenile fiction; Animals -- Fiction; Christmas stories; Dogs -- Juvenile fiction; Florida -- Juvenile fiction